The Indigo Book A Manual of Legal Citation - Sprigman, Christopher Jon (Open textbook library., 2016)
Welcome to The Indigo Book 2.0—a free, Creative Commons-dedicated implementation of the uniform system of citation commonly used in United States legal documents. The Indigo Book (2d ed. 2021) isn’t the same as The Bluebook: A Uniform System of Citation (21st ed. 2020), but it does implement the same system of citation that The Bluebook does. The scope of The Indigo Book’s coverage is roughly equivalent to The Bluebook’s “Bluepages”—that is, The Indigo Book covers legal citation for U.S. legal materials, as well as books, periodicals, and Internet and other electronic resources. For the materials that it covers, anyone using The Indigo Book will produce briefs, memoranda, law review articles, and other legal documents with citations that are compatible with the Uniform System of Citation. Although law students, scholars, and legal professionals sometimes talk about legal citation as if it is truly uniform, the fact is that legal citation has never actually been a uniform national system. Accordingly, The Indigo Book also provides insight into some of the discretionary preferences and jurisdiction specific variations found in legal citation throughout the United States.